2021
DOI: 10.1073/pnas.2102675118
|View full text |Cite
|
Sign up to set email alerts
|

Efficient integration of transmembrane domains depends on the folding properties of the upstream sequences

Abstract: The topology of most membrane proteins is defined by the successive integration of α-helical transmembrane domains at the Sec61 translocon. The translocon provides a pore for the transfer of polypeptide segments across the membrane while giving them lateral access to the lipid. For each polypeptide segment of ∼20 residues, the combined hydrophobicities of its constituent amino acids were previously shown to define the extent of membrane integration. Here, we discovered that different sequences preceding a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Our analysis focused specifically on SARS-CoV-2 ORF3a and ORF7a as both of these proteins are predicted to localize to the secretory pathway and could post-translationally impact antigen presentation by MHC-I. ORF3a has a topology that suggests it can integrate into lipid bilayers (14, 15), and studies in liposomes showed that it is permeable to cations such as calcium ions indicating that it is a viroporin (15). ORF7a has an N-terminal signal peptide and one putative transmembrane domain, indicating it is membrane associated(16).…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis focused specifically on SARS-CoV-2 ORF3a and ORF7a as both of these proteins are predicted to localize to the secretory pathway and could post-translationally impact antigen presentation by MHC-I. ORF3a has a topology that suggests it can integrate into lipid bilayers (14, 15), and studies in liposomes showed that it is permeable to cations such as calcium ions indicating that it is a viroporin (15). ORF7a has an N-terminal signal peptide and one putative transmembrane domain, indicating it is membrane associated(16).…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis focused specifically on SARS-CoV-2 ORF3a and ORF7a as both of these proteins are predicted to localize to the secretory pathway and could post-translationally impact antigen presentation by MHC-I. ORF3a has a topology that suggests that it can integrate into lipid bilayers ( 14 , 15 ), and studies in liposomes showed that it is permeable to cations such as calcium ions indicating that it is a viroporin ( 15 ). ORF7a has an N-terminal signal peptide and one putative transmembrane domain, indicating it is membrane associated ( 16 ).…”
mentioning
confidence: 99%
“…Mutations in these regions do not affect the overall mode of action of the protein [ 16 ]. On the other hand, they are seen as having their own role in the mechanism of function of membrane proteins [ 17 , 18 ]. Focusing on the TMDs, therefore, the search space can be limited to focus on the TMDs only.…”
Section: Introductionmentioning
confidence: 99%